2019
DOI: 10.1039/c9ta00192a
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium chloride–metal hydride based reaction cycle for vehicular applications

Abstract: A cost effective stationary fuel has been developed using mixtures of ammonium chloride and metal hydrides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…It is convenient to highlight that there was no other peak corresponding to the loss of structural water for this sample, which occurred during the zeolite calcination at 500°C. It should be noted that other studies have reported the decomposition of NH 4 Cl at 310°C [89]. Based on the DTG curve of CH-MS, it was concluded that this compound was not present in the modified zeolite.…”
Section: Resultsmentioning
confidence: 90%
“…It is convenient to highlight that there was no other peak corresponding to the loss of structural water for this sample, which occurred during the zeolite calcination at 500°C. It should be noted that other studies have reported the decomposition of NH 4 Cl at 310°C [89]. Based on the DTG curve of CH-MS, it was concluded that this compound was not present in the modified zeolite.…”
Section: Resultsmentioning
confidence: 90%